The Effect of Couples’ Interaction on Their Marital Satisfaction: A Qualitative Study - Tavakol, Zeinab; Yadollahi, Parvin; Shirmohammadi, Maryam; Karami Dehkordi, Akram (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: A healthy family is a family in which, people have a healthy growth and have a normal interpersonal relationship. This study aimed to determine the effect of couples’ interaction on their marital satisfaction among Iranian couples. Materials and Methods: A qualitative study using a conventional content analysis approach was used. Semi-structured interviews with 20 participants were conducted by purposive sampling. All of the interviews were recorded and then transcribed. Using MAXQDA software, the data were categorized, and the main themes and sub-themes were extracted. Results: Data analysis revealed three themes of “couples’ empathic interaction”, “social interaction”, and “family influence”. The theme of couples’ empathic interaction consisted of two sub-themes of sexual and non-sexual interaction. The theme of social interaction consisted of two sub-themes of interaction with children and interaction with colleagues, and the theme of family influence consisted of two sub-themes of supportive family and interfering family. Conclusions: The results showed that, by empathetic interaction, improving social interactions and proper use of family influence, we can help couples to achieve marital satisfaction. Providers of consultancy services to couples should learn about the influence of families on couples’ life and give them appropriate counseling and advice to improve their interaction and increase their independence from their families.